2020
DOI: 10.31185/eduj.vol1.iss40.1570
|View full text |Cite
|
Sign up to set email alerts
|

The Metaphorical Modeling of COVID-19 Pandemic Crisis in Infosphere Online News Articles

Abstract: The article addresses the process of metaphorical modeling of Coronavirus (COVID-19) during COVID-19 Pandemic Crisis (CPC) by  Infosphere Online News (INFON) articles and stories. It is a cognitive semantic analysis of the language of online news based on the theoretical constructs proposed by Lakoff & Johnson (1987) Conceptual Metapor Theory. INFON articles embody a process of transferring verbalized knowledge between two active parties (News Authorship and Readership) with unequal knwoeldge accessibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…An insight into the specialized bibliography reveals that the increasing use of military metaphors in both the Western and Asian media discourse has piqued the interest of many researchers, usually in medical reports, of cancer 23 . Of course, in the current context, they have also been analyzed in connection to the media coverage of the coronavirus pandemic (Craig, 2020;Al Husain, 2020;Yang, 2020;Olimat, 2020;Rafi, 2020;Rajandran, 2020).…”
Section: Covid-19 Through the Filter Of Metaphors In Military Terminomentioning
confidence: 99%
“…An insight into the specialized bibliography reveals that the increasing use of military metaphors in both the Western and Asian media discourse has piqued the interest of many researchers, usually in medical reports, of cancer 23 . Of course, in the current context, they have also been analyzed in connection to the media coverage of the coronavirus pandemic (Craig, 2020;Al Husain, 2020;Yang, 2020;Olimat, 2020;Rafi, 2020;Rajandran, 2020).…”
Section: Covid-19 Through the Filter Of Metaphors In Military Terminomentioning
confidence: 99%
“…O incursiune în bibliografia de specialitate relevă faptul că exploatarea metaforelor militare atît în discursul mediatic occidental, cît și în cel asiatic, a constituit obiectul de investigație al multor cercetări, de regulă în raportările din domeniul medical, al cancerului 23 . Desigur, în contextul actual, au fost analizate și în relație cu mediatizarea pandemiei de coronavirus (Craig, 2020;Al Husain, 2020;Yang, 2020;Olimat, 2020;Rafi, 2020;Rajandran, 2020).…”
Section: Personificare • De Obicei Clișeul Personificator îNregistreazăunclassified
“…Likewise, Saban (2008) states that metaphor is a specific mental schema that is reflected on another mental schema via establishing a relationship between two phenomena which are not similar. In modern cognitive semantics metaphor is a conceptual modelling device, being a mental operation that cognize, conceptualize, categorize, evaluate, and explain the world by analogy (Al Husain, 2020). For Cameron (1996) metaphors serve many different purposes and are highly effective in organizing information for individuals and societies.…”
Section: Introductionmentioning
confidence: 99%
“…Al Husain (2020) addresses the metaphorical expressions of Coronavirus by exploring the Infosphere Online News (INFON) articles and stories. After cognitive semantic analysis of the language of this news, it is found that INFON articles embody knowledge between two active parties (News Authorship and Readership).…”
Section: Introductionmentioning
confidence: 99%